Exploring the Internal Structure of the Achievement Emotion Questionnaire: Mathematics (AEQ-M) in Finnish Secondary Education Data - Sydänmaanlakka, Anni; Häsä, Jokke; Holm, Marja; Hannula, Markku S. (LUMAT-B: International Journal on Math, Science and Technology Education, 2025)
The control-value theory of achievement emotions (CVT) posits that students experience a range of emotions in academic contexts that are organized setting-dependant ways. Our aim was to examine the internal structure of the Finnish version of the Achievement Emotion Questionnaire –Mathematics (AEQ-M) with two datasets from upper secondary education. Our sample comprised a total of 2235 students (1418 students in 2021 and 1042 students in 2022 datasets) from 19 upper secondary schools across Finland. Confirmatory factor analysis showed identification issues with the seven-emotions-three-settings factor model, primarily due to issues with the hopelessness factor. After excluding hopelessness, the six-emotions-three-settings factor model fit our data well. These results provide evidence for the organization of achievement emotions in setting-dependent patterns. Further research is needed to determine whether the issues with the complete CVT factor model are attributed to, for example, cultural influences or the appropriateness of the measurement instrument.